PRINCIPLES OF BUSINESS MODEL IN INNOVATIVE ENTREPRENEURSHIP AND METHODS OF ITS ORGANIZATION - Rasulova Dilfuza Valievna; Khudoyberdieva Sadokat Shakirovna (European Science Publishing, 2024)
Entrepreneurship can be defined as the search for new areas of capital allocation, the improvement of production of existing products and the creation of new ones, the development of personal priorities, and the effective use of various opportunities for earning income. At the same time, entrepreneurship is defined as a mandatory use in the production of new products for the market, changing the field of activity or establishing a new enterprise or industry.
Keywords: entrepreneurship, capital, product, innovation, technology, employment, income